Strategi Marketing Mix Syariah Dalam Meningkatkan dan Mempertahankan Nasabah pada Produk Simpanan Idul Fitri di BMT Matra Pekalongan: Strategi Bauran Pemasaran Syariah dalam Meningkatkan dan Mempertahankan Nasabah pada Produk Simpanan Hari Raya di BMT Matra Pekalongan - Versiandika Pratama; Eka Frendika (Universitas Nahdlatul Ulama Sidoarjo, 2024)
This research aims to find out how the sharia marketing mix strategy is in increasing and maintaining the number of customers in Eid al-Fitr savings products at the BMT Matra Kajen Pekalongan Branch Office. This research is classified as qualitative research. The data sources used are primary data sources and data collection methods using observation, interviews and documentation obtained from informants. The results of this research in increasing the number of customers using 9P include: product strategy, the most popular product is sifitri. Price strategy: The deposit amount is returned in full without any deductions. Strategic location strategy on the side of the main road. Promotions strategy through word of mouth and WhatsApp groups. The people strategy adheres to the principles of honesty and attractive appearance. Strategy process for picking up the ball. Physical evidence strategy: facilities in the form of waiting chairs, air-conditioned rooms, parking areas. The promise strategy provides a promise of basic food supplies and a complete return of the deposit. The patience strategy is always being patient in the transaction process with customers. The strategy for retaining Sifitri product customers is a product strategy by innovating Sifitri products. The price strategy is no deductions and deposits are returned in full. The place strategy is easy to reach for customers from the surrounding area. Promotions strategy by carrying out intensive communication and follow up with Sifitri customers. The people strategy prioritizes friendliness and politeness. The transaction process strategy must be honest and thorough. Physical evidence strategy: the room is air-conditioned, clean and has a prayer room. The promise strategy provides parcels and deposits in full. The patience strategy must always be patient in the service process and not get angry easily